Functionality monitoring in youth sledge hockey - Baryaev, A. A.; Ivanov, A. V.; Aranson, M. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze benefits of the key physical fitness and functionality tests applicable in the youth sledge hockey sport. Methods and structure of the study. Modern sledge hockey gives a special priority to many physical qualities including speed (response rates, motor speed, startup movement speed, specific action speed etc.), dexterity (movement coordination, muscular sensations, spatial orientation, relaxation skills), endurance (special and speed keeping), plus explosive strength and active flexibility. It should be emphasized that the health tests and training progress test systems should produce extensive progress stage-specific physical fitness and functionality test data arrays for analyses.